2000
DOI: 10.1083/jcb.148.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 and Rac Stimulate Exocytosis of Secretory Granules by Activating the Ip3/Calcium Pathway in Rbl-2h3 Mast Cells

Abstract: We have expressed dominant-active and dominant-negative forms of the Rho GTPases, Cdc42 and Rac, using vaccinia virus to evaluate the effects of these mutants on the signaling pathway leading to the degranulation of secretory granules in RBL-2H3 cells. Dominant-active Cdc42 and Rac enhance antigen-stimulated secretion by about twofold, whereas the dominant-negative mutants significantly inhibit secretion. Interestingly, treatment with the calcium ionophore, A23187, and the PKC activator, PMA, rescues the inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
127
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 51 publications
8
127
1
Order By: Relevance
“…Small GTPases Rac1, Rac2, and Cdc42 have been implicated in granule exocytosis in mast cells and neutrophils through modulation of the actin cytoskeleton (43,44) and have been associated with cytokine secretion in other cells, such as IL-8 from polarized epithelial cells (45). However, no specific role for Rho GTPases in cytokine secretion from SMC has yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Small GTPases Rac1, Rac2, and Cdc42 have been implicated in granule exocytosis in mast cells and neutrophils through modulation of the actin cytoskeleton (43,44) and have been associated with cytokine secretion in other cells, such as IL-8 from polarized epithelial cells (45). However, no specific role for Rho GTPases in cytokine secretion from SMC has yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…In mast and chromaffin cells, one or more members of the Rho family play an active role in the exocytotic process (27,28,59,60). In addition, Cdc42 and Rac control regulated secretion in pancreatic ␤-cells (61).…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of Rac into permeabilized mast cells causes exocytic secretion [19], and expression of dominant-negative forms of Rac and Cdc42 inhibits antigen-mediated degranulation [20]. This inhibition is rescued by the addition of calcium ionophores, implying that Rac and Cdc42 are upstream of the calcium influx pathway [21,22]. Patch clamp studies in the same system showed that Rac/ Cdc42 are involved in calcium mobilization, in part through the regulation of calcium release-activated calcium channels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the activation of Rho GTPases is PI3K-independent in RBL-2H3 cells [24]. PLCc was found to directly bind Cdc42 in vitro in these cells [21], suggesting that PLCc could be a downstream effector of Rho GTPases in response to antigen stimulation. In contrast, we have here examined the role of PLCc in the upstream regulation of Rac and Cdc42.…”
Section: Introductionmentioning
confidence: 99%